EMS-STARS: Emergency Medical Services "Superuser" Transport Associations: An Adult Retrospective Study. (1st January 2015) - Hall, M. Kennedy; Raven, Maria C.; Hall, Jane; Yeh, Clement; Allen, Elaine; Rodriguez, Robert M.; Tangherlini, Niels L.; Sporer, Karl A.; Brown, John F.
Abstract Objective. Emergency medical services (EMS) "superusers" –those who use EMS services at extremely high rates –have not been well characterized. Recent interest in the small group of individuals who account for a disproportionate share of health-care expenditures has led to research on frequent users of emergency departments and other health services, but little research has been done regarding those who use EMS services. To inform policy and intervention implementation, we undertook a descriptive analysis of EMS superusers in a large urban community. In this paper we compare EMS superusers to low, moderate, and high users to characterize factors contributing to EMS use. We also estimate the financial impact of EMS superusers. Methods. We conducted a retrospective cross-sectional study based on 1 year of data from an urban EMS system. Data for all EMS encounters with patients age ≥18 years were extracted from electronic records generated on scene by paramedics. We identified demographic and clinical variables associated with levels of EMS use. EMS users were characterized by the annual number of EMS encounters: low (1), moderate (2–4), high (5–14), and superusers (≥15). In addition, we performed a financial analysis using San Francisco Fire Department (SFFD) 2009 charge and reimbursement data. Results. A total of 31, 462 adults generated 43, 559 EMS ambulance encounters, which resulted in 39, 107 transports (a 90% transport rate). Encounters for general medical reasons were common among moderate and high users and less frequent among superusers and low users, while alcohol use was exponentially correlated with encounter frequency. Superusers were significantly younger than moderate EMS users, and more likely to be male. The superuser group created a significantly higher financial burden/person than any other group, comprising 0.3% of the study population, but over 6% of annual EMS charges and reimbursements. Conclusions. In this retrospective study, adult EMS "superusers" emerged as a distinct, predominantly male population and their EMS encounters were associated with alcohol use. Continued analysis of this unique, high-cost, and frequently transported population will likely illuminate specific intervention strategies.